PANDANGAN PELAKU PENDIDIKAN DI UNIVERSITAS TERHADAP PEMBERLAKUAN MASYARAKAT EKONOMI ASEAN 2015 - Benedicta Evienia; Elnath Aldi; Astri Madhyaratri (Bina Ekonomi, 2014)
The implementation of the Asean Economic Community (AEC) in 2015 is a challenge that must be faced by all universities across the ASEAN countries, especially in Indonesia. Attempts to prepare graduates is important to be prepared. This study sought to see the perpetrators preparedness education in the Faculty of Economics Atma Jaya Jakarta in an attempt to anticipate the implementation of the ASEAN Economic Community, especially the ASEAN MRA Framework on accountancy services. The findings indicate that educational actors have learned and prepare to welcome the implementation of Asean Economic Community (AEC) findings also indicate that the addition of capacity and capability of the students is absolutely necessary in order to compete.